NGMIP: network-based global mobility support. (1st January 2012) - Yan, Zhiwei; Lee, Jong-Hyouk; Wang, Liming
In this paper, a network-based global mobility support protocol, named NGMIP, is introduced that combines advantages of both mobile IPv6 and proxy mobile IPv6 to provide inter-domain handovers to mobile nodes having no IP mobility stack modification. A hierarchical network architecture supporting both local and global mobility is presented with explanations of handover and packet transmission procedures. Performance analysis has been carried to confirm the proposed protocol's performance in terms of handover latency and protocol operation cost. From the performance analysis, we find that NGMIP outperforms other existing approaches for global mobility both on the handover latency and protocol cost.